Tenofovir Versus Placebo to Prevent Perinatal Transmission of Hepatitis B. Issue 8 (August 2018) - Jourdain, Gonzague; Ngo-Giang-Huong, Nicole; Harrison, Linda; Decker, Luc; Khamduang, Woottichai; Tierney, Camlin; Salvadori, Nicolas; Cressey, Tim R.; Sirirungsi, Wasna; Achalapong, Jullapong; Yuthavisuthi, Prapap; Kanjanavikai, Prateep; et al.
Abstract : (Abstracted from N Engl J Med 2018;378:911–923) (Pregnant women with an elevated viral load (>200, 000 IU/mL) of hepatitis B virus (HBV), or with a positive Hg e antigen (HBeAg) status, have a risk of transmitting infection to their infants, despite the infants' receiving hepatitis B immune globulin (HBIG). Antiviral agents that inhibit HBV replication, such as lamivudine, tenofovir disoproxil fumarate (TDF), and telbivudine, when administered to pregnant women with a high HBV viral load, may reduce the risk of mother-to-child transmission.